Regulating Transmission : Why System Operators Must Be Truly Independent - Arizu, Beatriz; Dunn, William H, Jr.; Tenenbaum, Bernard (World Bank, Washington, DC, 2012)
Which is best for effective competition in power sectors, a separate system operator, a joint-owner operator, or some combination of the two? The question is being hotly debated among power reformers. The answer? Both types of system operators can be made to work, singly or in combination. What is critical is that the system operators be truly independent of ownership and control of market participants -- generators, distributors and suppliers. but in many countries they have not been.